Fractional Calculus: Models, Algorithms, Technology - Machado, J.A. Tenreiro (Discontinuity, Nonlinearity, and Complexity, 2026)
In the last three decades Fractional Calculus (FC) became an area of intense research and development. The accompanying poster illustrates the present day major achievements in the application of FC in physics, engineering and biology.